Design for information : an introduction to the histories, theories, and best practices behind effective information visualizations - Meirelles, Isabel (Rockport, 2013)
Annotation The visualization process doesn't happen in a vacuum; it is grounded in principles and methodologies of design, cognition, perception, and human-computer-interaction that are combined to one's personal knowledge and creative experiences. Design for Informationcritically examines other design solutions --current and historic-- helping you gain a larger understanding of how to solve specific problems. This book is designed to help you foster the development of a repertoire of existing methods and concepts to help you overcome design problems. Learn the ins and outs of data visualization with this informative book that provides you with a series of current visualization case studies. The visualizations discussed are analyzed for their design principles and methods, giving you valuable critical and analytical tools to further develop your design process. The case study format of this book is perfect for discussing the histories, theories and best practices in the field through real-world, effective visualizations. The selection represents a fraction of effective visualizations that we encounter in this burgeoning field, allowing you the opportunity to extend your study to other solutions in your specific field(s) of practice. This book is also helpful to students in other disciplines who are involved with visualizing information, such as those in the digital humanities and most of the sciences.- Resumé vydavatel
Keywords: vizualizace informací; grafický design; infografika; information visualization; graphic design; infographics; elektronické knihy; monografie; electronic books; monographs